Rancang Bangun Thermoelectric Generator (TEG) Sebagai Suplai Daya Alternatif Germinasi Kacang Hijau - Ridzki, Imron; Hariz Santoso, Asfari; Awan Setiawan; Wijaya Kusuma (Politeknik Negeri Malang, 2024)
The central government has established the National Energy Policy (KEN) to increase the utilization of renewable energy sources (EBT) by around 23% by 2025 and 31% by 2050. In an effort to support the government's program, researchers have developed a Thermoelectric Generator (TEG) as an alternative power supply to replace the energy source from PT PLN for electrical equipment used in the green bean germination process such as lights, fans, and water pumps. This prototype consists of two chambers: a combustion chamber that generates electrical energy and a control room for the germination process. These two areas are separated to ensure that the control device and germination process are not affected by the heat from combustion. The main components of this prototype include ten TEG units with a maximum power of 5.2 W, a 33 Ah battery, an 8A Buck-boost converter, a 3A Buck converter, a 6W Full Spectrum LED, four DC fans, and a DC pump. The TEG functions effectively as the germination process proceeds smoothly.